2013
DOI: 10.1210/jc.2013-2281
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Two Mitotane Starting Dose Regimens in Patients With Advanced Adrenocortical Carcinoma

Abstract: The high-dose starting regimen resulted in neither significantly different mitotane levels nor a different rate of adverse events, but concomitant chemotherapy influenced these results. Thus, for mitotane monotherapy the high-dose approach is favorable, whereas for combination therapy a lower dose seems reasonable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
58
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(60 citation statements)
references
References 28 publications
0
58
0
1
Order By: Relevance
“…Mitotane might therefore, through its deleterious effect on mitochondria, inhibit gonadal steroidogenesis, in addition to its established effect on the adrenal cortex (4, 7). Evidence of an effect on testicular steroidogenesis has indeed been reported, thereby strengthening this hypothesis (8,12). These authors showed a decrease in testosterone levels in men, associated with an increase in circulating LH levels, suggesting impaired Leydig cell steroidogenesis.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Mitotane might therefore, through its deleterious effect on mitochondria, inhibit gonadal steroidogenesis, in addition to its established effect on the adrenal cortex (4, 7). Evidence of an effect on testicular steroidogenesis has indeed been reported, thereby strengthening this hypothesis (8,12). These authors showed a decrease in testosterone levels in men, associated with an increase in circulating LH levels, suggesting impaired Leydig cell steroidogenesis.…”
Section: Discussionmentioning
confidence: 64%
“…One unresolved question is whether the inhibitory effect of this drug on steroidogenesis is specific to the adrenal cortex or also concerns other steroidogenic glands such as the gonads. Some recent studies suggest that the testicles may be affected (8), but the ovarian effects of mitotane have not yet been studied, despite the fact that Cushing's disease (CD) and adrenocortical carcinomas (ACCs) are more common in women and can occur before the menopause. In this study, we describe for the first time the ovarian hormonal and gonadotropic impact of mitotane in 21 premenopausal patients.…”
Section: Introductionmentioning
confidence: 99%
“…3; Terzolo & Berruti 2008, Hermsen et al 2011, Terzolo et al 2013. Kerkhofs et al (2013c), who investigated the optimal dosing strategy, showed that 50% (10/20) of patients from the high dose starting regimen and 33% (4/12) of patients from the low-dose regimen reached the therapeutic level within 3 months. No significant differences were observed in frequency and severity of adverse events.…”
Section: Current Therapeutic Strategiesmentioning
confidence: 99%
“…In order to limit drug toxicity, 20 mg/l is considered the upper limit of the therapeutic window (9). In general, the build-up of plasma levels is slow, taking 3-4 months on average, but interindividual differences are large (11,12,13). As knowledge on mitotane pharmacokinetics is sparse, current dosing regimens are based on clinical experience and adjusted according to plasma levels and tolerability.…”
Section: Introductionmentioning
confidence: 99%